Fatigue and psychological distress in Chinese patients with hemodialysis: a moderated mediation model of cognitive decline and psychological flexibility - Zhenhua Jiang; Xiuli Qiao; Yang Li; Wenkui Sun; Hui Sun; Hui Zhang; Yue Bao; Liping Zong (BMC Psychiatry)
Abstract Background Fatigue and psychological distress are prevalent symptoms in hemodialysis (HD) patients, but the psychological mechanisms underlying these symptoms are not well understood. Cognitive decline and psychological flexibility may play significant roles in the emotional regulation processes associated with fatigue and psychological distress. This study aimed to explore whether cognitive decline mediates the association between fatigue and psychological distress, and whether mental flexibility plays a moderating role in this mediating effect. Methods A cross-sectional study using a convenience sample of 283 HD patients was conducted. Participants completed a self-administered, structured questionnaire that assessed socio-demographic and clinical variables, fatigue, cognitive decline, psychological flexibility, and psychological distress. Results The mediation analysis revealed that cognitive decline partially mediated the relationship between fatigue and psychological distress. Moderated mediation analysis showed that psychological flexibility significantly moderated both the direct effects of fatigue and cognitive decline on psychological distress, as well as the indirect effect of fatigue on psychological distress through cognitive decline. Specifically, as levels of psychological flexibility increased, both the direct and indirect effects decreased significantly. Conclusion The results show that psychological flexibility plays an important role in buffering the negative effects of fatigue and cognitive decline on psychological distress. Moreover, these findings suggest that acceptance and commitment therapy (ACT) intervention in HD patients can help maintain their mental health. Clinical trial number Not applicable.